Green building financing - Pavlo Brunko (Cхід, 2016)
The article is devoted to the problem of green buildings financing. It is noted that bank lending can be a major source of funds for construction. However, current trends in the economy of Ukraine shows that credit, especially lending to construction, is in poor condition. Accordingly, there is a need to explore the possibility of additional measures that can be applied to bringing financial resources into the construction.